TRADE AND PEACE: POLITICAL FORCES ARRANGEMENT IS DEFINED BY ECONOMIC INTERCONNECTION - E. Zenkina; V. Kutovoi (Вестник университета)
In this article has revealed, that the strengthening of economic interdependence between trading partners promotes to decreasing in tension between neighbouring states, and development of freedom of movement of goods, services, people and the capitals can facilitate permission of political and territorial disputes. Particularly, continuation of partner states complex and system working on practical cooperation in spheres of economy, will undoubtedly render additional political effect on member states of the Eurasian economic union for the account of development of mutual trade. It has noted, that today both the states, and enterprise community come to awareness of need an integration transformations of the Eurasian economic space.